TREND IN TUNA LANDINGS BY THE LONGLINE FISHERY OPERATING OUT ON BENOA, BALI - T.L.O. Davis; Sofri Bahar; Nurzali Naamin; J.H. Farley; D. Le (Research Center for Fisheries, 1999)
The number of longline vessels operabing out of Port of Benoa, Bali has increased steadily since 1986. However, this increase has been more rapid since 1994, and in 1996 there were 528 vessels registered in the port.